Enhancing Proppant Properties of Silica from Rupat Island Using Epoxy and Polyester Resins: A Comparative Study Based on API 19C - -, Novrianti; Faroq, Muhammad; Indra, Rezi; Purnamawati, Neneng (Aceh International Journal of Science and Technology, 2025)
This study evaluates the potential of silica sand from Rupat Island, Indonesia, as a natural proppant for hydraulic fracturing, based on API RP 19C standards. Samples tested include unmodified sand, epoxy-coated sand (5% and 10%), and polyester-coated sand (5% and 10%). Key parameters assessed were roundness and sphericity, bulk density, turbidity, acid solubility, and crush resistance. Uncoated silica showed substandard morphology (0.47), while resin-coated samples reached 0.53 and polyester resin reached 0.54, meeting API criteria. Bulk density ranged from 1.53 to 1.60 g/cc, and turbidity values (2038 NTU) were within acceptable limits. This study demonstrates that applying a resin coating to Rupat silica sand notably enhances its physical and chemical properties, making it more suitable for use as a proppant. The coated sand exhibited an increase in bulk density, reaching 1.581.60 0.01 g/cc, which exceeds the API RP 19C minimum standard of 1.5 g/cc and suggests improved packing efficiency. Additionally, the acid solubility dropped from 2.8% in the uncoated sand to 1.22 0.01% in the coated samples, reflecting greater chemical resistance. Turbidity levels remained low, ranging from 20 to 135 2 NTU, well below the API limit of 250 NTU, indicating minimal generation of fine particles. In crush resistance tests, uncoated sand lost up to 13% weight at 5000 psi, while resin-coated variants showed improved performance, with weight loss reduced to 814% (5 mL and 10 mL epoxy resin) and 512% (5 mL and 10 mL polyester) at 6000 psi and 8000 psi. These results confirm that with appropriate surface modification, Rupat silica sand meets key API 19C criteria and holds strong potential as a local proppant material for hydraulic fracturingTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian// TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//